Playing in childhood: importance and singularities for children with visual impairment (Práxis Educativa, 2017)
This study investigated what kind of playing and how visually impaired children play in the family and educational contexts, aiming at understanding playing and the role of toys in these children’s development. The study was based on the historical-cultural perspective, mainly considering Vygotsky’s studies. Empirical material was collected from five families with blind or short-sighted children and from the specialized institution these children attend. We adopted semi-structured interviews with parents and educators and observation of the relevant contexts. The data collected was categorized and theorized through content analysis. We concluded that the mediation of another person during playing enables the visually impaired child to develop confidence to explore the physical space, objects and to elaborate concepts. Keywords: Visually impaired children. Playing. Social interaction.